IBM Storage Solutions for IBM Cloud Private Blueprint (IBM, 2019)
IBM Storage Solutions for IBM Cloud™ Private delivers a blueprint for multicloud architecture. IBM, delivering solutions to help you win. In this blueprint, learn how to: Combine the benefits of IBM Systems with the performance of IBM Storage solutions so that you can deliver the right services to your clients today. Deliver optimized private cloud services ahead of schedule and under budget with a complete IBM Cloud Private stack. Containerize applications and deliver the SLAs that your team needs to thrive and win. Implement IBM Cloud Private to deploy modern applications like blockchain and AI or modernize what you already have. You now have the capabilities. This edition applies to IBM Storage Solutions for IBM Cloud Private Version 1 Release 5.0.